Effect of balloon therapy v/s spirometry in promotion of respiratory function in children with respiratory infection - Sreeletha, Arunima (International Journal of Nursing Research, 2023)
Respiratory diseases are very common in children, especially the respiratory infection. It’s one of the leading causes of morbidity and mortality in young children. In India acute respiratory infection is one of the major causes of childhood death. This study is to assess effect of balloon therapy v/s incentive spirometry in promotion of respiratory function among children with Acute Respiratory Infections (ARI) in NMMC Hospital Vashi. The aim of the study is to explore the effect of balloon therapy and incentive spirometry in promotion of pulmonary function in children with acute respiratory infections and also compare the effect of both interventions. The objectives were to assess the respiratory function, to find out the effect of balloon therapy and incentive spirometry, to find out association between selected demographic variables with balloon therapy and spirometry and to compare the effect of balloon therapy and incentive spirometry among children with ARI. Quasi experimental two group pre-test and post-test design was used. 40 children from the age group of 2- 6 years with ARI were the samples in this study. In both interventions the pulmonary function got improved along with routine treatment. The researchers found balloon therapy seems more effective in reducing respiratory symptoms in children with respiratory problems in comparison with spirometry. As the data supports balloon therapy is more effective than spirometry. During the data collection process the researcher experienced that balloon therapy was more acceptable among children as it is a part of their normal routine play activity and excitement to explore blowing balloons and few children expressed anxiety and fear towards spirometry. So the researcher strongly suggests approaching the hospitalized sick children with acceptable form of innovative therapeutic regimen for their complete participation in their health care.